Conversion coating pretreatment enhances pipeline integrity (2018)
It is necessary to coat both the internal and external surfaces of pipelines which transport different types of fluids that are usually contaminated with various percentages of aggressive corrosives. Pipelines pass through various terrains and highly challenging environments hence the need for both internal and external coatings to prevent corrosion and its adverse effects. In order to improve on the longevity of pipelines and the adhesion of the coating system, it is preferable to conversion coat blasted surfaces prior to application of any coating system. Improvements in pipeline coatings applications and the often neglected chromating procedure prior to coating application have been highlighted. This will prolong the lifespan of pipeline networks and secure these strategic assets from being a source of both materials and human resources drain pipes. However, the use of corrosion resistant alloys as internal lining for carbon steel pipes in the petroleum/gas industry is fast gaining recognition.